Practical wisdom: How do personal virtue beliefs and contextual factors interact in adolescents' moral decision-making? - Briggs, Claire; Lumsdon, David (Journal of moral education, 2022)
Adolescence has been highlighted as a significant period in an individual's character development and autonomous decision-making. Social cognitive theories of character emphasise the importance of the interaction between person and context in making decisions which promote the good. A Grounded Theory methodology was used to explore how adolescents apply their virtue beliefs when faced with moral dilemmas, an ability which has been called 'practical wisdom' in some theories of character development. Eighteen participants aged 12-15 took part in interviews to explore their moral decision-making processes. The findings suggest the interaction between adolescents' virtue beliefs and contextual factors can vary according to the individual's prior experience, the factors salient to them within the immediate context (particularly social and emotional factors) and the weight they assign to possible consequences of their decisions. The study concludes that adolescents' moral decision-making processes vary between individuals and across situations, with social cognitive theories of decision-making offering a possible explanation for these variations.